Capital Structure and Stock Prices: Empirical Evidence from Listed Beverage, Food and Tobacco Companies in Sri Lanka - Subramaniam, V.A.; Anandasayanan, S. (International Journal of Social and Administrative Sciences, 2018)
The share price of a firm is affected by various factors. Determination of share price is not an easy task. The share price movement is based on the firm’s fundamentals, Market efficiency, Macroeconomic Indicators and Perception of the Investors. Several studies have proven that share price of firms are explained by its capital structure. This study tests the relationship between capital structure and share prices of the listed Food and Beverage Tobacco companies in CSE for the period from 2011/2012 to 2016/2017. It analyzes the relationship between share price and capital structure by employing panel least square method approach. According to the results of the study there is a positive relationship between debt to equity and share prices .The results were statistically significant at 1% level of significance. The results indicate adding debt to overall capital positively effects on the share prices. These findings have important implications for managers or people who take decisions regarding capital structure. The changes in capital structure may have a significant impact on stock prices of the companies.